A study protocol for a randomised controlled feasibility trial of an intervention to increase activity and reduce sedentary behaviour in people with severe mental illness: Walking fOR Health (WORtH) Study - Suzanne M. McDonough (BMC, 2021)
Abstract Background People with severe mental illness (SMI) are less physically active and more sedentary than healthy controls, contributing to poorer physical health outcomes in this population. There is a need to understand the feasibility and acceptability, and explore the effective components, of health behaviour change interventions targeting physical activity and sedentary behaviour in this population in rural and semi-rural settings. Methods This 13-week randomised controlled feasibility trial compares the Walking fOR Health (WORtH) multi-component behaviour change intervention, which includes education, goal-setting and self-monitoring, with a one-off education session. It aims to recruit 60 inactive adults with SMI via three community mental health teams in Ireland and Northern Ireland. Primary outcomes are related to feasibility and acceptability, including recruitment, retention and adherence rates, adverse events and qualitative feedback from participants and clinicians. Secondary outcome measures include self-reported and accelerometer-measured physical activity and sedentary behaviour, anthropometry measures, physical function and mental wellbeing. A mixed-methods process evaluation will be undertaken. This study protocol outlines changes to the study in response to the COVID-19 pandemic. Discussion This study will address the challenges and implications of remote delivery of the WORtH intervention due to the COVID-19 pandemic and inform the design of a future definitive randomised controlled trial if it is shown to be feasible. Trial registration The trial was registered on clinicaltrials.gov ( NCT04134871 ) on 22 October 2019.